PENGARUH KETEBALAN DIAMETER ZEOLIT DIGUNAKAN SEBAGAI MEDIA FILTER TERGHADAP PENURUNAN KESADAHAN AIR SUMUR ARTETIS DI KELURAHAN SENDANGGUWO KECAMATAN TEMBALANG KOTA SEMARANG - Mifbakhuddin -; Ratih Sari Wardani; Atfis Prihandono Rozaq (Jurnal Kesehatan Masyarakat Indonesia, 2008)
The Influence of Zeolite Diameter Thickness Used As Filter Media on the Decrease of the Lime Content of Deep Well Water (xiii+ 40 page + 8 tables + 1 graph + 5 picture + 7 appendices) Background : Based on the survey that was made it was found that 90% of the population in RW(Community Unit) II, Kelurahan Sendangguwo use of deep well water as clean water and drinking water. They assume that the deep well water is cleaner and better in quality compared to shallow well water or tap water, so that the deep water water is also used for cooking and drinking. Based on the examination of the deep well water, the level of lime content is 512.7 mg CaCO3 / l which is above the tolerable minimum threshold of 500 mg/l. Based on the problem, the researcher conducted a research on zeolite as filter media to reduce of the level content of CaCO3 with a different size of diameter i.e., 2 mm, 1 mm and 0.5 mm. Objective : To find out the influence of the diameter size of the zeolite on the decrease of the CaCo3 level content of the deep well water Method : The type of research being used was a True Experiment with randomized experimental design, or is also called randomized pretest-posttest control group design. The diameter sizes of zeolite used in this research as water ion change media were 2 mm, 1 mm, 0.5 mm diameter respectively, and used nine times with the test results. The total sample being examined was 27 samples. Independent variable in this research is the diameter variation of the zeolite used, and the dependent variable is the decrease level content of CaCO3 hardness and confounding variables are pH and temperature. The research used descriptive analysis to determine the percentage reduction of CaCO3 level content and statistical analysis using Kruskal-Wallis test to determine the influence of the size of the different diameter of zeolite. Result : The percentage decrease of content level of CaCO3 of the deep well water after passing the zeolite filter is in average 84.57% in the treatment with ziolite of 2 mm in diameter and 77.38% in the treatment with zeolite of 1 mm, and flat - average 95.95% in the treatment with 0.5 mm diameter zeolite. The most effective Zeolit in lowering level content of CaCO3 of deep well water is on the size of 0.5 mm diameter. Results of Kruskal-Wallis test showed p value = 0.000 which means that it is smaller than the value of α 0.05, so there is significant influence of the different size in diameter of ziolite on the decline of the level content of CaCO3 of the deep well water. Conclusion: There is significant influence of the different size in diameter of zeolite used as filter media, on the decline of level content of CaCO3 of deep well water (P = 0.000). The most effective Zeolit in lowering level content of CaCO3 of deep well water is the 0.5 mm size in diameter of zeolite.   Key word : Level content of CaCO3, Ziolite Diameter, Level Content Decrease